Kenya : Requests for an Extended Arrangement Under the Extended Fund Facility and an Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Kenya. (IMF Staff Country Reports; Country Report, 2021)
Kenya has been hit hard by the COVID-19 pandemic. Despite a forceful policy response by the authorities, the socio-economic impact has been significant. The shock has also exacerbated the country's pre-existing fiscal vulnerabilities, pushing Kenya into high risk of debt distress. While the economy is now recovering, fiscal and balance-of-payments financing needs remain sizable over the medium term.